IMPLEMENTATION OF PASSWORD SENDING VIA SEMAPHORE FLAG TO COMMUNICATE MEMBERS SCOUT - Naura Ayu Sabilla; Arum Dewi Rahayu; Isma Canda Ningtyas P (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques used in this research are as follows: (1) Observation (Observation, documentation and traiangulation. Research results. In terms of communication, in the maritime or scouting sector, communication techniques using the Semaphore language are still used. flag. The flag semaphore is a system for sending information over long distances in the form of visual signals using a small flag, stick, or hand. The information is then interpreted in the position of the flag. Seeing the flag semaphore which is still used today, language training hardware was created Flag semaphore is deemed necessary to help train learning of the codes used in the flag semaphore language.